Magnesium alloy high-pressure-resistance surface treatment liquid and preparation method thereof

By using silicone modified aqueous epoxy resin, modified hexagonal boron nitride and modified graphene on the surface of the magnesium alloy material used in the energy storage battery case, the problem of poor corrosion, insulation and heat dissipation effects of magnesium alloy material in the energy storage battery case application is solved, and the formation of high-voltage resistance, excellent insulation and high thermal conductivity coatings are achieved.

CN119662091AActive Publication Date: 2025-03-21HEFEI HUAQING FANGXING SURFACING TECH CO LTD

Patent Information

Application Number
CN202411923386.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Existing magnesium alloy materials have problems of corrosion, insulation and heat dissipation in energy storage battery case applications, which are difficult to meet the needs of high pressure resistance, lightweight and efficient heat dissipation.

Method used

Silicone modified aqueous epoxy resin is used as the basic film forming liquid, and modified hexagonal boron nitride and modified graphene are added on the basis, and the high-pressure resistance surface treatment liquid is formed by ultrasonic dispersion and high-speed dispersion shearing machine.

Benefits of technology

The high pressure resistance, excellent insulation and high thermal conductivity coating on the surface of magnesium alloy materials is achieved, and the corrosion resistance, adhesion and heat dissipation effect of magnesium alloy in energy storage battery shell applications is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of insulation heat dissipation coatings, and particularly relates to a magnesium alloy high-pressure-resistance surface treatment liquid and a preparation method thereof. The coating comprises the following raw materials in parts by weight: 30-40 parts of organic silicon modified waterborne epoxy resin, 9-12 parts of modified hexagonal boron nitride, 10-15 parts of modified graphene, 2-4 parts of a curing agent, 0.5-2 parts of a flatting agent, 1-2 parts of a defoaming agent and 25-50 parts of acetone. A coating formed on the surface of a magnesium alloy base material through the magnesium alloy high-pressure-resistance surface treatment liquid has high volume resistance, high breakdown voltage resistance, high corrosion resistance and high heat conductivity coefficient, and the magnesium alloy high-pressure-resistance surface treatment liquid can be applied to the field of new energy and can also be applied to the fields of aerospace, 3C electronics and the like. And the market prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of insulating heat dissipation coatings, and specifically relates to a magnesium alloy high-pressure resistance surface treatment liquid and a preparation method thereof. Background Art

[0002] Energy storage batteries are mainly composed of battery modules, battery management systems (BMS) and shells. Battery modules include positive and negative electrode materials, electrolytes, diaphragms, etc., and are the core of the battery; the battery management system (BMS) is responsible for monitoring the status of the battery to ensure its safe and reliable operation; the shell is the protective layer of the energy storage battery, which plays a role in protecting the internal structure of the battery and needs to have insulation, corrosion resistance, heat dissipation and other functions. As the carrier of the battery module, the battery shell plays a key role in the safety and protection of the battery module.

[0003] At present, common materials for energy storage battery shells include aluminum alloy, stainless steel, ABS flame-retardant plastic, etc., which can play a certain role in protecting batteries. However, with the increase in battery energy density and the increase in battery modules, the proportion of battery shell structure is also increasing, which makes the overall weight of energy storage batteries continue to grow. Therefore, under the development trend of "lightweight" for energy saving and carbon reduction, and the implementation of relevant development policies for "lightweight" materials-magnesium alloys, magnesium alloy materials with low density, light weight, high specific strength and specific stiffness, strong impact resistance, and electromagnetic shielding have broad market prospects in the application field of energy storage battery shells. According to market research, the total weight of aluminum alloy structural parts used in a certain brand of battery is about 125 kilograms. If all magnesium alloys are used, the weight is expected to be reduced to 80 kilograms, and the weight reduction effect will reach 30%. However, magnesium alloy materials are active and prone to corrosion. At the same time, due to the particularity of the application scenarios in the field of energy storage battery shells, magnesium alloy materials are also required to have good insulation and heat dissipation effects. The main way to achieve these functions is to coat thermally conductive insulating composite materials on their surface. At present, thermally conductive insulating composite materials are divided into intrinsic thermally conductive insulating composite materials and filled thermally conductive insulating composite materials. The preparation process of intrinsic thermal conductive insulating composite materials is complex, with high technical difficulty, and the improvement of heat dissipation effect is limited; the preparation process of filled thermal conductive insulating composite materials is simple and easy to use for industrial large-scale production, which is the key research direction in the future. However, there is an inverse relationship between thermal conductivity and breakdown voltage resistance of filled thermal conductive insulating composite materials at present; at the same time, the improvement of battery energy density and charge and discharge power makes the existing filled thermal conductive insulating composite materials unable to meet the market requirements for insulation and other indicators. Summary of the invention

[0004] In view of the application requirements of magnesium alloys in the field of energy storage batteries, the present invention provides a magnesium alloy high-pressure resistance surface treatment liquid and a preparation method thereof, aiming to enable lightweight magnesium alloy materials to have excellent pressure resistance, corrosion resistance, heat dissipation and other properties.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A magnesium alloy high pressure resistance surface treatment liquid, the composition of its raw materials in parts by weight is as follows:

[0007] 30-40 parts of silicone modified waterborne epoxy resin;

[0008] 9-12 parts of modified hexagonal boron nitride;

[0009] 10-15 parts of modified graphene;

[0010] 2-4 parts of curing agent;

[0011] Leveling agent 0.5-2 parts;

[0012] 1-2 parts of defoaming agent;

[0013] 25-50 parts of acetone.

[0014] Preferably, the organosilicon-modified waterborne epoxy resin is prepared according to the following steps:

[0015] S1. Add polyethylene glycol, catalyst, maleic anhydride and propylene glycol methyl ether acetate into a three-necked flask, connect nitrogen to exhaust the air, heat to 80-90°C under nitrogen protection, stir magnetically at a rate of 600-800r / min for 8-10h, then add epoxy resin, heat to 100-120°C, continue stirring and reacting for 2-3h to obtain epoxy resin emulsifier, wherein the amount ratio of polyethylene glycol, catalyst, maleic anhydride, propylene glycol methyl ether acetate and epoxy resin is 40-50g:0.5-1.5g:5-8g:200-250mL:16-21g;

[0016] S2. Add epoxy resin and epoxy resin emulsifier into a three-necked flask, heat to 65-75°C, use a high-speed dispersing shearing machine to disperse at a rate of 1000-1200r / min, and simultaneously add high-purity water at a rate of 1-2mL / min. After the addition is completed, increase the dispersion rate to 1500-1600r / min, continue to disperse for 1-2h, and obtain an aqueous epoxy resin dispersion; wherein the amount ratio of epoxy resin, epoxy resin emulsifier and high-purity water is 70-80g:7-8g:130-150mL;

[0017] S3. Add butyl acetate to the aqueous epoxy resin dispersion, place in a constant temperature oil bath at 35-50°C, and stir at a rate of 400-600r / min until fully dissolved; then add organosilane, dibutyltin dilaurate, and triethylamine in sequence, raise the temperature to 70-80°C, and continue stirring for 5-6h to obtain an organosilicon-modified aqueous epoxy resin; wherein the amount ratio of aqueous epoxy resin dispersion, butyl acetate, organosilane, dibutyltin dilaurate, and triethylamine is 50-60g:150-180mL:1.5-2.5g:0.3-0.6g:10-15g.

[0018] Preferably, in step S1, the catalyst is any one of potassium persulfate, boron trifluoride ethyl ether, and triphenylphosphine, or a mixture of any two of them in any mass ratio.

[0019] Preferably, in the step of preparing the organosilicon-modified waterborne epoxy resin, the organosilane is any one of methyltriethoxysilane, dimethyldichlorosilane, phenyltrichlorosilane, and diphenyldichlorosilane, or a mixture of any two of them in any mass ratio.

[0020] Preferably, the modified hexagonal boron nitride is prepared according to the following steps:

[0021] (1) adding hexagonal boron nitride h-BN powder to isopropanol solvent, oscillating in an ultrasonic water bath at room temperature for 10-12 hours, then adding NaOH, heating to 110-130°C, and stirring at a constant temperature for 22-24 hours to obtain hydroxylated h-BN-OH; washing with high-purity water and filtering until the filtrate is neutral; vacuum drying the filter cake at 65-70°C for 22-24 hours to obtain hydroxylated hexagonal boron nitride solid h-BN-OH, grinding it into powder for standby use; wherein the amount ratio of hexagonal boron nitride, isopropanol and NaOH is 10-14g:200-250mL:20-28g;

[0022] (2) Add h-BN-OH powder and mercaptopropyl trimethoxysilane MPMS into a three-necked flask and disperse them in toluene by ultrasonic for 20-30 min at room temperature. 2 Under protection, the temperature is raised to 100-110°C and stirred in an oil bath for reflux for 6-8h, the solid product is filtered, washed with anhydrous ethanol, filtered 3-5 times, and vacuum dried at 65-70°C for 22-24h to obtain grafted h-BN-MPMS; wherein the amount ratio of h-BN-OH powder, MPMS and toluene is 1.5-2g:1-3mL:200-250mL;

[0023] (3) h-BN-MPMS, glycidyl methacrylate (GMA) and dimethylformamide (DMF) were added to a three-necked flask in sequence. 2Under the atmosphere, stir evenly at 600-800r / min, heat to 55-65℃, quickly add dibenzoyl peroxide BPO, continue to keep constant temperature stirring for 10-12h, and obtain modified hexagonal boron nitride, recorded as h-BN-PGMA; wherein, the usage ratio of h-BN-MPMS, GMA, DMF, and BPO is 1-2g:10-20mL:150-200mL:0.08-0.1g.

[0024] Preferably, the modified graphene is prepared according to the following steps:

[0025] Step 1, adding graphene oxide and organosilane to anhydrous ethanol, ultrasonically dispersing at room temperature for 1-2 hours, then heating to 100-110°C, reflux in an oil bath for 10-12 hours, cooling to room temperature and filtering, repeatedly washing the filter residue with ethanol and filtering it 3 times, and finally drying it in an oven at 65-75°C for 0.5-1h to obtain silane-modified graphene oxide; wherein the amount ratio of graphene oxide, organosilane and anhydrous ethanol is 2-4g:4-8mL:100-150mL;

[0026] Step 2, adding silane-modified graphene oxide to an ethanol aqueous solution, ultrasonically dispersing it at room temperature for 1-2 hours, adding ammonia water, continuing ultrasonically dispersing it for 1-2 hours, slowly adding tetraethoxysilane TEOS ethanol aqueous solution, magnetically stirring at 60-65°C for 10-12 hours, using a high-speed centrifuge to centrifuge at 7000-8000r / min for 5-10 minutes, washing and filtering the precipitate with high-purity water, and drying it in an oven at 70-75°C for 2-3 hours to obtain modified graphene; wherein the amount ratio of silane-modified graphene oxide, ethanol aqueous solution, ammonia water, and TEOS ethanol aqueous solution is 1-2g:400-500mL:100-150mL:12-24mL, the ethanol aqueous solution is composed of ethanol and water in a volume ratio of 1:1, and the volume ratio of TEOS to ethanol aqueous solution in the TEOS ethanol aqueous solution is 1:2.

[0027] Preferably, in the modified graphene preparation step, the organosilane is at least one of 3-(2-aminoethylamino)propyltrimethoxysilane AAPTS, N,N-diethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0028] Preferably, the curing agent is any one of succinic anhydride, ethylenediamine, and 4,4′-diaminodiphenyl sulfone, or a mixture of any two of them in any mass ratio; the leveling agent is any one of polymethyl alkyl siloxane, dimethyl polysiloxane, polyether-modified polydimethyl siloxane, and polyether-modified polymethyl alkyl siloxane, or a mixture of any two of them in any mass ratio; the defoaming agent is any one of DF-2162, W-052, DF6800, BASF-1293, and A-10 defoaming agents, or a mixture of any two of them in any mass ratio.

[0029] The method for preparing the magnesium alloy high pressure resistance surface treatment liquid of the present invention comprises the following steps:

[0030] Step 1: Weigh each raw material by weight;

[0031] Step 2: Add the modified hexagonal boron nitride to acetone, then add the modified graphene, ultrasonically disperse for 1-2 hours, add the silicone-modified water-based epoxy resin, curing agent, leveling agent, and defoaming agent in sequence, heat to 60-70°C, stir at a constant temperature of 1200-1500r / min for 0.5-1h, and cool to room temperature to obtain a magnesium alloy high pressure resistance surface treatment liquid.

[0032] The magnesium alloy high pressure resistance surface treatment liquid of the present invention can be used in energy storage battery casings.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] (1) The present invention uses a water-based epoxy resin modified with organic silicon as the base film-forming liquid, and adds hexagonal boron nitride and modified graphene oxide modified by free radical polymerization grafting. The modified hexagonal boron nitride and graphene oxide have a significant effect on improving the high pressure resistance and heat dissipation of the coating, and the two have a synergistic effect.

[0035] (2) The present invention improves the dispersibility of epoxy resin by using epoxy resin emulsifier, increases water-based and silicone modification pathways, introduces silicone active groups into water-based epoxy resin, forms a cross-linked network, improves the adhesion and aging resistance of water-based epoxy resin, reduces the interfacial tension between epoxy resin and filler, and improves the corrosion resistance and adhesion of the coating.

[0036] (3) The coating formed by the treatment solution in the embodiment of the present invention on the surface of the magnesium alloy substrate has a thickness of 60-80 μm and a volume resistivity of 1.42×10 15Ω·cm, breakdown voltage 6213V, thermal conductivity 1.413W / (m·k), neutral salt spray test 720h, adhesion level 0. Therefore, the coating formed on the surface of the magnesium alloy substrate by the magnesium alloy high pressure resistance surface treatment liquid of the present invention has high volume resistance, high breakdown voltage, high corrosion resistance and high thermal conductivity, which solves the problems of poor corrosion resistance, poor heat dissipation effect and poor pressure resistance existing in the existing energy storage battery shell materials.

[0037] (4) The magnesium alloy high pressure resistance surface treatment liquid obtained by the present invention can be applied not only to the field of new energy, but also to the fields of aerospace, 3C electronics, etc., and has broad market prospects. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the embodiments to illustrate the features and advantages of the present invention. The following embodiments are not intended to limit the present invention, and the formulations compiled by professionals in the field based on the ideas and raw material ratios of the present invention also fall within the protection scope of the present invention.

[0039] The organosilicon-modified waterborne epoxy resin, modified hexagonal boron nitride, modified graphene and magnesium alloy high-pressure-resistant surface treatment liquid involved in the following examples and comparative examples are prepared according to the following steps:

[0040] Preparation of silicone-modified waterborne epoxy resin:

[0041] S1. Add 50 g of polyethylene glycol, 0.5 g of potassium persulfate, 5 g of maleic anhydride, and 200 mL of propylene glycol methyl ether acetate into a three-necked flask, connect nitrogen to exhaust the air, raise the temperature to 90 ° C under nitrogen protection, and stir magnetically at a rate of 800 r / min for 10 h. Then add 21 g of epoxy resin (bisphenol A type E-44, epoxide value 0.47), raise the temperature to 120 ° C, and continue stirring the reaction for 2 h to obtain an epoxy resin emulsifier.

[0042] S2. Add 80 g of epoxy resin (bisphenol A type E-44) and 8 g of epoxy resin emulsifier into a three-necked flask, heat to 65°C, use a high-speed dispersing shearing machine to disperse at a rate of 1200 r / min, and at the same time, add 150 mL of high-purity water (resistivity (25°C) ≥18 MΩ·cm) at a rate of 1-2 mL / min. After the addition is completed, increase the dispersion rate to 1500 r / min and continue dispersing for 1 hour to obtain an aqueous epoxy resin dispersion.

[0043] S3. Take 50g of water-based epoxy resin dispersion, add 150mL of butyl acetate, place in a constant temperature oil bath at 35°C, and stir at a rate of 400r / min until fully dissolved; then add 2.5g of methyltriethoxysilane, 0.6g of dibutyltin dilaurate, and 15g of triethylamine in sequence, raise the temperature to 70°C, and continue stirring the reaction for 5h to obtain a silicone-modified water-based epoxy resin.

[0044] The modified hexagonal boron nitride is prepared according to the following steps:

[0045] (1) 10 g of h-BN powder (purity> 99%, particle size 1 μm) was added to 200 mL of isopropanol solvent, and ultrasonically shaken in a water bath at room temperature for 12 h, then 20 g of NaOH was added, the temperature was raised to 130° C., and the mixture was stirred at constant temperature for 24 h to obtain hydroxylated h-BN-OH; the mixture was washed with high-purity water (resistivity (25° C.) ≥ 18 MΩ·cm) and filtered until the filtrate was neutral; the filter cake was vacuum dried at 70° C. for 24 h to obtain hydroxylated hexagonal boron nitride solid (h-BN-OH), which was ground into powder for later use.

[0046] (2) Add 2 g of h-BN-OH powder and 1 mL of MPMS into a three-necked flask and disperse them in 250 mL of toluene by ultrasonic for 20 min at room temperature. 2 Under protection, the temperature was raised to 110°C and refluxed in an oil bath with stirring for 8 h. The solid product was filtered out, washed with anhydrous ethanol and filtered three times, and dried in a vacuum at 70°C for 24 h to obtain grafted h-BN-MPMS.

[0047] (3) 2 g of h-BN-MPMS, 20 mL of GMA and 200 mL of DMF were added to a three-necked flask in sequence. 2 Under atmosphere, stir evenly at 800 r / min, heat to 55 °C, quickly add 0.1 g of BPO, and continue to stir at constant temperature for 12 h to obtain h-BN–PGMA.

[0048] The modified graphene was prepared according to the following steps:

[0049] Step 1. Take 2 g GO (purity>99wt%, flake diameter 20μm) and 4 mL 3-aminopropyltrimethoxysilane, add them to 100 mL anhydrous ethanol, ultrasonically disperse at room temperature for 1 hour, then heat to 110°C, reflux in an oil bath for 12 hours, cool to room temperature and filter, wash the residue with ethanol and filter it three times, and finally dry it in an oven at 75°C for 30 minutes to obtain silane-modified graphene oxide.

[0050] Step 2, take 1g of silane-modified graphene oxide, add 400mL of ethanol aqueous solution (composed of ethanol and water in a volume ratio of 1:1), ultrasonically disperse at room temperature for 1h, add 100mL of ammonia water, continue ultrasonically dispersing for 1h, slowly add 12mL of tetraethoxysilane (TEOS) ethanol aqueous solution (the volume ratio of TEOS to ethanol aqueous solution is 1:2, and the ethanol aqueous solution is composed of ethanol and water in a volume ratio of 1:1), magnetically stir at 60°C for 12h, use a high-speed centrifuge to centrifuge at 8000r / min for 10min, wash and filter the precipitate with high-purity water, and dry it in an oven at 75°C for 2h to obtain modified graphene.

[0051] The high pressure resistance surface treatment liquid of magnesium alloy is prepared according to the following steps:

[0052] Step 1: Weigh each raw material by weight.

[0053] Step 2: Add the modified hexagonal boron nitride to acetone, then add the modified graphene, ultrasonically disperse for 1 hour, add silicone-modified water-based epoxy resin, curing agent, leveling agent, and defoaming agent in sequence, heat to 60°C, stir at a constant temperature of 1500r / min for 30 minutes, and cool to room temperature to obtain a high-pressure-resistant surface treatment liquid for magnesium alloy.

[0054] Example 1

[0055] A magnesium alloy high-pressure-resistant surface treatment liquid, wherein the raw materials are composed of 40 parts of organic silicon-modified waterborne epoxy resin, 12 parts of modified hexagonal boron nitride, 15 parts of modified graphene, 4 parts of succinic anhydride, 2 parts of polyether-modified polydimethylsiloxane, 2 parts of W-052 defoaming agent, and 25 parts of acetone in parts by weight.

[0056] Example 2

[0057] A magnesium alloy high-pressure-resistant surface treatment liquid, wherein the raw materials are composed of 35 parts of organic silicon-modified waterborne epoxy resin, 10 parts of modified hexagonal boron nitride, 12 parts of modified graphene, 3 parts of succinic anhydride, 1 part of polyether-modified polydimethylsiloxane, 1 part of W-052 defoaming agent, and 38 parts of acetone in parts by weight.

[0058] Example 3

[0059] A magnesium alloy high-pressure-resistant surface treatment liquid, wherein the raw materials are composed of 30 parts of organic silicon-modified waterborne epoxy resin, 9 parts of modified hexagonal boron nitride, 10 parts of modified graphene, 2 parts of succinic anhydride, 0.5 parts of polyether-modified polydimethylsiloxane, 1 part of W-052 defoaming agent, and 47.5 parts of acetone in parts by weight.

[0060] Comparative Example 1

[0061] The components of the magnesium alloy high pressure resistance surface treatment liquid configured in this comparative example are the same as those in Example 1, except that the organosilicon-modified waterborne epoxy resin is replaced by epoxy resin (bisphenol A type E-44).

[0062] Comparative Example 2

[0063] The components of the magnesium alloy high pressure resistance surface treatment liquid configured in this comparative example are the same as those in Example 1, except that the addition amount of modified hexagonal boron nitride is 0.

[0064] Comparative Example 3

[0065] The components of the magnesium alloy high pressure resistance surface treatment liquid configured in this comparative example are the same as those in Example 1, except that the amount of modified graphene added is 0.

[0066] Comparative Example 4

[0067] The components of the magnesium alloy high pressure resistance surface treatment liquid configured in this comparative example are the same as those in Example 1, except that the modified hexagonal boron nitride is replaced by hexagonal boron nitride (purity>99%, particle size 1 μm).

[0068] Comparative Example 5

[0069] The components of the magnesium alloy high pressure resistance surface treatment liquid configured in this comparative example are the same as those in Example 1, except that the modified graphene is replaced by graphene oxide (purity>99wt%, flake diameter 20μm).

[0070] The magnesium alloy high pressure resistance surface treatment liquid prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was used to form a coating on the surface of a magnesium alloy substrate according to the following method and the performance was tested.

[0071] The magnesium alloy substrate (AZ91D, 70*40*2mm) was sanded to a bright surface and then cleaned with acetone. After drying, the magnesium alloy substrate was completely immersed in the treatment liquid for 3 minutes at room temperature, taken out and hung vertically for 30 minutes, and the remaining paint on the bottom was scraped off with a scraper. The magnesium alloy substrate treated with the treatment liquid was placed in a 120℃ oven and dried for 4 hours. The coating thickness, volume resistance, breakdown voltage, thermal conductivity, corrosion resistance, and adhesion performance test methods are as follows.

[0072] Coating thickness: GB / T 13452.2-2008 "Determination of film thickness of paints and varnishes"

[0073] Volume resistance: GB / T 31838.2-2019 "Dielectric and resistance properties of solid insulating materials Part 2: Resistance characteristics (DC method) Volume resistance and volume resistivity"

[0074] Breakdown voltage: GB / T 1408.1-2016 "Electrical strength test methods for insulating materials Part 1: Tests at power frequency"

[0075] Thermal conductivity: GB / T 10297-2015 "Determination of thermal conductivity of non-metallic solid materials - Hot wire method"

[0076] Corrosion resistance: GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes" After 720 hours of neutral salt spray test, if there is no obvious rust, bubbles and cracks on the surface, it is qualified; if there is obvious rust, bubbles and cracks, it is unqualified.

[0077] Adhesion: GB / T 9286-2021 "Scratch test for paints and varnishes"

[0078] The test results of the coating properties formed on the surface of the magnesium alloy substrate by the treatment solutions configured in the above-mentioned embodiments and comparative examples are shown in Table 1.

[0079] Table 1 Coating performance test results

[0080] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Coating thickness, μm 71 69 78 76 72 72 73 71 Volume resistivity, Ω·cm <![CDATA[1.42×10 15 ]]> <![CDATA[1.39×10 15 ]]> <![CDATA[1.35×10 15 ]]> <![CDATA[1.31×10 15 ]]> <![CDATA[1.22×10 14 ]]> <![CDATA[1.31×10 13 ]]> <![CDATA[1.33×10 14 ]]> <![CDATA[1.96×10 13 ]]> Breakdown voltage, V 6213 6135 6093 6034 5733 5336 5866 5574 Thermal conductivity, W / (m·k) 1.413 1.398 1.362 0.910 0.742 0.812 0.864 0.902 Corrosion resistance (NSS, 720h) qualified qualified qualified Failure Failure qualified qualified qualified Adhesion, Grade 0 0 0 2 0 0 0 0

[0081] According to Table 1, we can see that:

[0082] It can be seen from Examples 1 to 3 that the coating formed on the surface of the magnesium alloy substrate by the magnesium alloy high pressure resistant surface treatment liquid prepared by the present invention has high breakdown voltage, volume resistance and thermal conductivity, excellent surface adhesion and corrosion resistance. It can be seen from Example 1 and Comparative Example 1 that the present invention selects organosilane to modify the waterborne epoxy resin, thereby improving the corrosion resistance and adhesion of the coating. This is because the active groups of organosilicon are introduced into the waterborne epoxy resin to form a cross-linked network, thereby improving the adhesion and anti-aging properties of the waterborne epoxy resin. It can be seen from Example 1 and Comparative Examples 1 and 2 that the present invention selects modified hexagonal boron nitride as a thermally conductive filler, thereby improving the thermal conductivity of the coating. This is because the organosilicon-modified waterborne epoxy resin and the modified hexagonal boron nitride improve the compatibility between them and reduce the interfacial tension. At the same time, the modified hexagonal boron nitride constructs a three-dimensional thermally conductive network structure in the epoxy resin system, thereby enhancing the thermal conductivity effect. As can be seen from Example 1, Comparative Examples 1 and 3, the present invention selects insulating modified graphene as an insulating filler to improve the volume resistivity and breakdown voltage of the coating, because the organic silicon-modified waterborne epoxy resin and the modified graphene improve the compatibility between them, and the modified graphene shields its conductivity. As can be seen from Example 1, Comparative Examples 2 and 3, the present invention selects organic silicon to modify the waterborne epoxy resin, and the modified hexagonal boron nitride and modified graphene as insulating thermal conductive fillers to improve the insulation and thermal conductivity of the coating, because the synergistic effect of the modified hexagonal boron nitride and graphene makes the coating have better insulation and heat dissipation effects. As can be seen from Example 1 and Comparative Example 4, the present invention selects to modify the hexagonal boron nitride to improve the thermal conductivity of the coating, because the polymer chain is modified and grafted on the surface of the hexagonal boron nitride, and an interconnected thermal conductive network is formed inside. It can be seen from Example 1 and Comparative Example 5 that the present invention chooses to modify graphene oxide, thereby improving the volume resistance and breakdown voltage of the coating. This is because the modification enables the graphene oxide to form an insulating closed layer, thereby improving its insulation performance.

[0083] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0084] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A magnesium alloy high pressure resistance surface treatment liquid, characterized in that: The composition of each raw material in parts by weight is as follows: 30-40 parts of silicone modified waterborne epoxy resin; 9-12 parts of modified hexagonal boron nitride; 10-15 parts of modified graphene; 2-4 parts of curing agent; Leveling agent 0.5-2 parts; 1-2 parts of defoaming agent; 25-50 parts of acetone.

2. The magnesium alloy high pressure resistance surface treatment liquid according to claim 1, characterized in that: The organosilicon-modified waterborne epoxy resin is prepared according to the following steps: S1. Add polyethylene glycol, catalyst, maleic anhydride and propylene glycol methyl ether acetate into a three-necked flask, connect nitrogen to exhaust the air, heat to 80-90°C under nitrogen protection, stir magnetically at a rate of 600-800r / min for 8-10h, then add epoxy resin, heat to 100-120°C, continue stirring and reacting for 2-3h to obtain epoxy resin emulsifier, wherein the amount ratio of polyethylene glycol, catalyst, maleic anhydride, propylene glycol methyl ether acetate and epoxy resin is 40-50g:0.5-1.5g:5-8g:200-250mL:16-21g; S2. Add epoxy resin and epoxy resin emulsifier into a three-necked flask, heat to 65-75°C, use a high-speed dispersing shearing machine to disperse at a rate of 1000-1200r / min, and simultaneously add high-purity water at a rate of 1-2mL / min. After the addition is completed, increase the dispersion rate to 1500-1600r / min, continue to disperse for 1-2h, and obtain an aqueous epoxy resin dispersion; wherein the amount ratio of epoxy resin, epoxy resin emulsifier and high-purity water is 70-80g:7-8g:130-150mL; S3. Add butyl acetate to the aqueous epoxy resin dispersion, place in a constant temperature oil bath at 35-50°C, and stir at a rate of 400-600r / min until fully dissolved; then add organosilane, dibutyltin dilaurate, and triethylamine in sequence, raise the temperature to 70-80°C, and continue stirring for 5-6h to obtain an organosilicon-modified aqueous epoxy resin; wherein the amount ratio of aqueous epoxy resin dispersion, butyl acetate, organosilane, dibutyltin dilaurate, and triethylamine is 50-60g:150-180mL:1.5-2.5g:0.3-0.6g:10-15g.

3. The magnesium alloy high pressure resistance surface treatment liquid according to claim 2, characterized in that: In step S1, the catalyst is any one of potassium persulfate, boron trifluoride ethyl ether, and triphenylphosphine, or a mixture of any two of them in any mass ratio.

4. The magnesium alloy high pressure resistance surface treatment liquid according to claim 2, characterized in that: In step S3, the organosilane is any one of methyltriethoxysilane, dimethyldichlorosilane, phenyltrichlorosilane, and diphenyldichlorosilane, or a mixture of any two of them in any mass ratio.

5. The magnesium alloy high pressure resistance surface treatment liquid according to claim 1, characterized in that: The modified hexagonal boron nitride is prepared according to the following steps: (1) adding hexagonal boron nitride h-BN powder to isopropanol solvent, oscillating in an ultrasonic water bath at room temperature for 10-12 hours, then adding NaOH, heating to 110-130°C, and stirring at a constant temperature for 22-24 hours to obtain hydroxylated h-BN-OH; washing with high-purity water and filtering until the filtrate is neutral; vacuum drying the filter cake at 65-70°C for 22-24 hours to obtain hydroxylated hexagonal boron nitride solid h-BN-OH, grinding it into powder for standby use; wherein the amount ratio of hexagonal boron nitride, isopropanol and NaOH is 10-14g:200-250mL:20-28g; (2) Add h-BN-OH powder and mercaptopropyltrimethoxysilane MPMS into a three-necked flask, ultrasonically disperse in toluene at room temperature for 20-30 minutes, heat to 100-110° C. in an oil bath with stirring and reflux for 6-8 hours under N2 protection, filter the solid product, wash with anhydrous ethanol, filter 3-5 times, and vacuum dry at 65-70° C. for 22-24 hours to obtain grafted h-BN-MPMS; wherein the amount ratio of h-BN-OH powder, MPMS and toluene is 1.5-2 g: 1-3 mL: 200-250 mL; (3) h-BN-MPMS, glycidyl methacrylate (GMA) and dimethylformamide (DMF) were added to a three-necked flask in sequence, and stirred evenly at 600-800 r / min under N2 atmosphere. When heated to 55-65°C, dibenzoyl peroxide (BPO) was quickly added, and the constant temperature stirring was continued for 10-12 hours to obtain modified hexagonal boron nitride, which was recorded as h-BN–PGMA. The dosage ratio of h-BN-MPMS, GMA, DMF and BPO was 1-2 g: 10-20 mL: 150-200 mL: 0.08-0.1 g.

6. The magnesium alloy high pressure resistance surface treatment liquid according to claim 1, characterized in that: The modified graphene is prepared according to the following steps: Step 1, adding graphene oxide and organosilane to anhydrous ethanol, ultrasonically dispersing at room temperature for 1-2 hours, then heating to 100-110°C, reflux in an oil bath for 10-12 hours, cooling to room temperature and filtering, repeatedly washing the filter residue with ethanol and filtering it 3 times, and finally drying it in an oven at 65-75°C for 0.5-1h to obtain silane-modified graphene oxide; wherein the amount ratio of graphene oxide, organosilane and anhydrous ethanol is 2-4g:4-8mL:100-150mL; Step 2, adding silane-modified graphene oxide to an ethanol aqueous solution, ultrasonically dispersing it at room temperature for 1-2 hours, adding ammonia water, continuing ultrasonically dispersing it for 1-2 hours, slowly adding tetraethoxysilane TEOS ethanol aqueous solution, magnetically stirring at 60-65°C for 10-12 hours, using a high-speed centrifuge to centrifuge at 7000-8000r / min for 5-10 minutes, washing and filtering the precipitate with high-purity water, and drying it in an oven at 70-75°C for 2-3 hours to obtain modified graphene; wherein the amount ratio of silane-modified graphene oxide, ethanol aqueous solution, ammonia water, and TEOS ethanol aqueous solution is 1-2g:400-500mL:100-150mL:12-24mL, the ethanol aqueous solution is composed of ethanol and water in a volume ratio of 1:1, and the volume ratio of TEOS to ethanol aqueous solution in the TEOS ethanol aqueous solution is 1:

2.

7. The magnesium alloy high pressure resistance surface treatment liquid according to claim 6, characterized in that: In the modified graphene preparation step, the organosilane is at least one of 3-(2-aminoethylamino)propyltrimethoxysilane AAPTS, N,N-diethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

8. The magnesium alloy high pressure resistance surface treatment liquid according to claim 1, characterized in that: The curing agent is any one of succinic anhydride, ethylenediamine, and 4,4′-diaminodiphenyl sulfone, or a mixture of any two of them in any mass ratio; the leveling agent is any one of polymethyl alkyl siloxane, dimethyl polysiloxane, polyether-modified polydimethyl siloxane, and polyether-modified polymethyl alkyl siloxane, or a mixture of any two of them in any mass ratio; the defoaming agent is any one of DF-2162, W-052, DF6800, BASF-1293, and A-10, or a mixture of any two of them in any mass ratio.

9. A method for preparing a magnesium alloy high pressure resistance surface treatment solution as claimed in any one of claims 1 to 8, characterized in that: The steps include: Step 1: Weigh each raw material by weight; Step 2: Add the modified hexagonal boron nitride to acetone, then add the modified graphene, ultrasonically disperse for 1-2 hours, add the silicone-modified water-based epoxy resin, curing agent, leveling agent, and defoaming agent in sequence, heat to 60-70°C, stir at a constant temperature of 1200-1500r / min for 0.5-1h, and cool to room temperature to obtain a magnesium alloy high pressure resistance surface treatment liquid.

Citation Information

Patent Citations

  • Graphene heat dissipation coating, aluminum plate radiator heat dissipation coating and preparation method

    CN109929352A

  • Corrosion-resistant heat conduction coating and preparation method thereof

    CN110305559A

  • Modified boron nitride grafted waterborne acrylic resin insulating material and preparation method thereof

    CN111484626A

  • Preparation method of graphene-based waterborne epoxy resin emulsion

    CN111808300A

  • Photoelectric composite cable

    CN114898929A

Cited By

  • Whisker-based insulating anticorrosive paint and preparation method thereof

    CN120041058A

  • Whisker-based insulating anticorrosive paint and method for preparing the same

    CN120041058B